CONCOMITANT FACTORS AFFECTING GESTATION LENGTH AND PERINATAL MORTALITY IN HOLSTEIN-FRIESIAN COWS - N. M. Bogas; A. V. Sherasiya; J. C. Simões (Ветеринария сегодня)
The objective of this study was to identify and quantify factors presenting simultaneous moderate or strong influence on gestation length and perinatal mortality (until 4 days postpartum) in Holstein-Frisian dams. The overall gestation length least square mean was 278.2 ± 0.2 days (n = 962). According to the multivariate model (p < 0.001), a shorter gestation length was observed in Holstein-Friesian (–2.0 days) and Red Holstein-Friesian (–3.9 days) breed sires whereas Brown Swiss (2.0 days) and Aberdeen-Angus (2.3 days) breed sires showed a longer gestation length. Primiparous cows and twin pregnancies, as well calving in June and July, shortened gestation length in –1.4, –4.0, –1.9 and –1.8 days, respectively. The perinatal mortality incidence was 7.4% (n = 72) and was more likely to occur in twin pregnancies (p < 0.01) than in pregnancies carrying female (odds ratio = 8.1) or male (odds ratio = 7.9) singletons, as well in primiparous (odds ratio = 2.6) than multiparous dams (p < 0.05). In conclusion, parity and twinning were the major factors which influenced simultaneously gestation length of dams and perinatal mortality incidence. Nevertheless, all studied factors had a significant impact on gestation length and should be considered for reproductive management programs of dairy herds.